NUTRIENT CONTENTS IN ‘TOMMY ATKINS’ MANGO LEAVES AT FLOWERING AND FRUITING STAGES - Leandro N. Faria; Sergio L. R. DONATO; Marcelo R. Dos Santos; Luciana G. Castro (Engenharia Agrícola, 2016)
ABSTRACT The objective of this study was to evaluate the nutrient contents in ‘Tommy Atkins’ mango leaves at the flowering and fruiting stages under different strategies to reduce irrigation levels during flower induction. Five irrigation level reduction strategies, based on crop evapotranspiration (ETc) were used in the plots: T1 (0% ETc), T2 (25% ETc), T3 (50% ETc), T4 (75% ETc) and T5 (100% ETc); two production cycles in the split-plots; and in two development stages, flowering and harvest, in the split-split plots. The content of N, P, K, Ca, Mg, and S, as well as B, Cu, Fe, Mn, Zn, and Na was determined and leaf chlorophyll index was measured during the second cycle. The content of P, K, Mg, and Cu in the ‘Tommy Atkins’ mango trees leaves varied according to phases and cycles, regardless of the strategies to reduce irrigation levels in floral induction. The contents of N, Ca, B, Fe, Mn, and Na varied with stages and with the production cycles, in an independent manner. Foliar N contents were above the sufficiency range at the different development stages and cycles evaluated. The indices of a, b, and total chlorophyll varied independent of reading time. The nutrient contents with lower mobility in the plant, Ca, B, Fe and Mn increase in ‘Tommy Atkins’ mango trees leaves from flowering to fruiting, with the return of irrigation at 100% crop evapotranspiration, while the levels of N, P, K and Mg, nutrients with high mobility in plant decrease.